A STUDY ON THE ABILITY OF SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU IN SUPPLYING CORRECT PUNCTUATIONS - Masria '; Afrianto '; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed at investigating the level of the students’ ability at English Study Program of Universitas Riau in supplying correct punctuations. The research design is a descriptive quantitative. There were 45 students chosen as the samples of this research. The instruments of the research were 30 multiple choice questions assessed by using Heaton’s formula that were analyzed by using Harris’ measurement. It was found that the average score of the students ability in supplying correct punctuations was 47,9. To be more specific the result finding shows that there were 3 (6,6%) students in excellent ability level. Then, there were 9 (20%) students who were in good ability level. Moreover, there were 12 (26,7%) students who were in mediocre ability level and there were 17 ( 37,8%) students who were in poor level. Last, there were 4 (8,9%) students who were in very poor level.Key Words: Student, Ability, Supply, Correct, Punctuayions